The Impact of Smartphone Use on Children Aged 5-6 Years - Eke Sumartin; Siti Misra Susanti; Rachman Saleh (Jurnal Caksana : Pendidikan Anak Usia Dini, 2026)
This study aims to identify the negative impacts of smartphone use on children aged 5–6 years and to examine parents' role in supervising smartphone use among children at TK Negeri 24 Buton, Waangu-Angu Village, Indonesia. The rapid advancement of digital technology has led to increased smartphone access among young children, raising concerns about developmental consequences, particularly during the critical golden age (0–6 years) when foundational social, emotional, and language skills are formed. This research employed a descriptive, qualitative approach to explore smartphone use in depth. Data were collected through observation, semi-structured interviews, and documentation. The research subjects consisted of 17 children aged 5–6 years, 1 classroom teacher, and parents as primary informants. Data analysis followed the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing, with validity ensured through source and technique triangulation. The findings revealed that excessive smartphone use negatively affects children's development, particularly in social, language, emotional, and behavioral domains. Children exhibited decreased social interaction, limited two-way communication skills, difficulty regulating emotions (e.g., tantrums when smartphone access was restricted), passive behavior, and dependency on devices. Additionally, children became more easily distracted and less focused during learning activities. The study also identified that parents play a crucial role in supervising smartphone use, including setting time limits, providing accompaniment during use, establishing clear rules (e.g., no smartphones before bedtime), and redirecting children to more positive and educational activities (e.g., outdoor play, drawing). The study concludes that uncontrolled smartphone use can significantly hinder child development; therefore, optimal parental supervision is essential to ensure that smartphone use remains directed, balanced, and does not compromise children's developmental outcomes. These findings contribute to early childhood education by providing empirical evidence from a rural Indonesian context and offering practical recommendations for parents and educators.